(untitled) (Kolej Universiti Sains dan Teknologi Malaysia)
This page presents the geographical name data for Sungai Terengganu in Malaysia, as supplied by the US military intelligence in electronic format, including the geographic coordinates and place name in various forms, latin, roman and native characters, and its location in its respective country's administrative division.
Keywords: Kỹ thuật sông,River engineering; Khía cạnh môi trường,Environmental aspects